Entsteht der Postkapitalismus im Kapitalismus? Eine Kritik an Masons Transformationsstrategie - Butollo, Florian; Kalff, Yannick (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2017)
Paul Mason has delivered a compelling analysis in which he argues that digital technologies, knowledge work and the corresponding failure of mechanisms of capital valorisation would undermine capitalism while implying a gradual emergence of social relations beyond capitalism. In our view, however, this proposal for a new transformation strategy is flawed because Mason underestimates tendencies of marketisation that grasp new forms of labour and overestimates the possibilities. In particular, we first criticize Mason’s understanding that valorisation in a knowledge-based, digitized capitalism is impossible. Second, we reject the idea that digital commons and valorisation are mutually exclusive by tracing processes of commodification in this field. Third, we offer a critique of Mason’s strategy for transformation, which we deem one-sided. He does not undertake a sober account of societal power relations and overstretches post-capitalistic potentials. Subjectivities are perceived as inherently capable of being emancipated and universally educated, which neglects the mutual dependence of structure and subjectivities and the way in which class relations and class struggle affect their constitution.